ASSOCIATION OF ALTERNATION IN INTESTINAL MICROBIOTA WITH IMPAIRED PSYCHOLOGICAL FUNCTION IN PATIENTS WITH INFLAMMATORY BOWEL DISEASES IN REMISSION - SHAHID, HA; MALIK, Z; MALIK, M (Biological and Clinical Sciences Research Journal, 2023)
The prospective study was conducted in the Department of Gastroenterology, THQ Hospital, from April 2021 to April 2022 to evaluate the association between mucosa-associated psychological functioning and intestinal microbiota in IBD remission patients. The study was conducted on 200 patients with comparable numbers of UC and CD. At inclusion, clinical phenotyping of disease status, including disease activity, was done using modified Truelove and Witt’s activity index (MTWAI) and CD activity index (CDAI). Biopsies were used for DNA extraction. The microbial profile of UC and CD patients was evaluated in correlation to depression. Like anxiety, the highest taxonomic changes were noted in the Firmicutes phylum. Many negative correlations were noted between the abundance of various taxa in Firmicutes phylum and depression. An analysis was conducted to determine the relationship between anxiety, the abundance of certain microbial taxa, and the quality of life (QoL) of individuals with Crohn's disease (CD) and ulcerative colitis (UC). The results showed that there was a significant correlation between anxiety and a relative increase of taxa in CD only. Additionally, the QoL of those with CD had a negative correlation with the increase in taxa. For UC, the relationship was partly accurate. However, higher QoL was associated with the abundance of the RF32 family and Sutterella, indicating that these taxa could be potential markers of favorable outcomes.